The Role of Halal Certification In The Digitalization Of Small And Medium Enterprise Students Of The Social Science Education Department Iain Syekh Nurjati Cirebon - Puspitasari, Ratna; Puspitasari, Euis; Resmalasari, Septiani (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
Globalization is characterized by the use of information and communication technology in the era of industrial revolution 4.0 as the basic capital needed by industrial players to develop businesses, including MSMEs in higher education. The problems in this research include: how to halal certification for student MSMEs and how to implement digitalization of small and medium enterprises among students. The halal theory from the World Halal Council (WHC) and halal certification bodies mentions ethical aspects in business so that producers operate honestly, fairly and transparently in line with Islamic principles. In the field of education, Freire's theory focuses on education as the main key to social empowerment because through education, people are able to develop abilities and skills to participate effectively in economic empowerment. Qualitative method research with a phenomenological approach explores halal certification, the development of student MSMEs, the Social Mart application and the implementation of digitalization of MSMEs. Firstly, the researcher observes and analyzes the phenomenon of halal certification with the digital economy which is the research topic, secondly determines the focus of the research based on the results of initial observations and interviews with entrepreneurial students. The three sources of data collected were observations, information from several entrepreneurs and course lecturers. The research results show that halal certification and digitalization of MSMEs have a positive impact on the development of MSMEs. has higher sales figures when compared to MSMEs that have not implemented digitalization because they have higher operational efficiency